Ebola Virus Transcription Activator VP30 Is a Zinc-Binding Protein - Modrof, Jens (American Society for Microbiology, 2003)
Ebola virus VP30 is an essential activator of viral transcription. In viral particles, VP30 is closely associated with the nucleocapsid complex. A conspicuous structural feature of VP30 is an unconventional zinc-binding Cys(3)-His motif comprising amino acids 68 to 95. By using a colorimetric zinc-binding assay we found that the VP30-specific Cys(3)-His motif stoichiometrically binds zinc ions in a one-to-one relationship. Substitution of the conserved cysteines and the histidine within the motif led to a complete loss of the capacity for zinc binding. Functional analyses revealed that none of the tested mutations of the proposed zinc-coordinating residues influenced binding of VP30 to nucleocapsid-like particles but, concerning its role in activating viral transcription, all resulted in a protein that was inactive.